2014
DOI: 10.1242/dev.111260
|View full text |Cite
|
Sign up to set email alerts
|

The tumor suppressor Nf2 regulates corpus callosum development by inhibiting the transcriptional coactivator Yap

Abstract: The corpus callosum connects cerebral hemispheres and is the largest axon tract in the mammalian brain. Callosal malformations are among the most common congenital brain anomalies and are associated with a wide range of neuropsychological deficits. Crossing of the midline by callosal axons relies on a proper midline environment that harbors guidepost cells emitting guidance cues to instruct callosal axon navigation. Little is known about what controls the formation of the midline environment. We find that two … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(22 citation statements)
references
References 71 publications
2
20
0
Order By: Relevance
“…Finally, comparison of mRNA levels between a prospective gyrus vs. a prospective sulcus of developing (postnatal day (P) 2) ferret neocortex, available in a previously published transcriptome dataset (De Juan Romero et al, 2015), showed that the Yap mRNA level was higher in the oSVZ of the prospective gyrus than the prospective sulcus ( Figure S1D), consistent with the notion that a relative increase in cNPC proliferation in this germinal zone contributes to gyrus formation (Hansen et al, 2010;Reillo et al, 2011;Wang et al, 2011). Taken together, these Yap/YAP mRNA data raised the possibility that YAP may not only have a role in the proliferation of APs, as previously shown for embryonic mouse neocortex (Lavado et al, 2013;Lavado et al, 2014), but that differences in the level of active YAP may underlie the differences in the proliferative capacity of mouse vs. ferret and human BPs.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Finally, comparison of mRNA levels between a prospective gyrus vs. a prospective sulcus of developing (postnatal day (P) 2) ferret neocortex, available in a previously published transcriptome dataset (De Juan Romero et al, 2015), showed that the Yap mRNA level was higher in the oSVZ of the prospective gyrus than the prospective sulcus ( Figure S1D), consistent with the notion that a relative increase in cNPC proliferation in this germinal zone contributes to gyrus formation (Hansen et al, 2010;Reillo et al, 2011;Wang et al, 2011). Taken together, these Yap/YAP mRNA data raised the possibility that YAP may not only have a role in the proliferation of APs, as previously shown for embryonic mouse neocortex (Lavado et al, 2013;Lavado et al, 2014), but that differences in the level of active YAP may underlie the differences in the proliferative capacity of mouse vs. ferret and human BPs.…”
Section: Resultssupporting
confidence: 85%
“…of YAP were confined to mouse brain development and concentrated on APs (Cappello et al, 2013;Lavado et al, 2013;Lavado et al, 2014;Saito et al, 2017). In contrast to these reports, the present study is focused on BPs and in this context has compared YAP expression and activity in the SVZ vs. VZ of developing neocortex of three mammals exhibiting a different extent of neocortex expansion -mouse, ferret and human.…”
Section: Differential Yap Expression Between Vz and Svz Across Speciementioning
confidence: 99%
See 1 more Smart Citation
“…), whereas telencephalon‐specific Nf2 KO embryos show expansion of neural progenitors with increased nuclear YAP1/TAZ (Lavado et al . , ).…”
Section: Brain and Nervous Systemmentioning
confidence: 99%
“…Mice heterozygous for mutated Nf2 do not develop neuronal malignancies, but homozygous Nf2 loss only in Schwann cells leads to their hyperplasia and eventually schwannomas (Giovannini et al 2000). Double loss of Nf2 plus one p53 allele drives the development of peripheral nerve sheath tumors (Robanus-Maandag et al 2004), whereas telencephalon-specific Nf2 KO embryos show expansion of neural progenitors with increased nuclear YAP1/TAZ (Lavado et al 2013(Lavado et al , 2014.…”
Section: Brain and Nervous Systemmentioning
confidence: 99%